2017
DOI: 10.2147/jpr.s142115
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical etiology of “pseudo-sciatica” from superior cluneal nerve entrapment: a laboratory investigation

Abstract: ObjectiveThe superior cluneal nerve (SCN) may become entrapped where it pierces the thoracolumbar fascia over the iliac crest; this can cause low back pain (LBP) and referred pain radiating into the posterior thigh, calf, and occasionally the foot, producing the condition known as “pseudo-sciatica.” Because the SCN was thought to be a cutaneous branch of the lumbar dorsal rami, originating from the dorsal roots of L1–L3, previous anatomical studies failed to explain why SCN causes “pseudo-sciatica”. The purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
0
21
0
4
Order By: Relevance
“…Buranın lokalizasyonu orta hatta spinöz çıkıntıların 7-8 cm lateralinde iliyak krest üzerindedir. [4][5][6][7][8][9][10][11][12][13][14][15][16] Anatomi çalışmalarında SKS'nin mediyal dalının osteofibröz tünelden geçmesi ile ilgili tartışmalı veriler vardır. Bazı çalışmalarda, SKS'nin bütün dallarının iliyak krest üzerinde torakolomber fasiyayı deldiği gösterilmiş; karşıt olarak başta Maigne olmak üzere, bazı araştırmacılar tüm mediyal dalların osteofibröz tünelden geçtiğini rapor ederken, diğer bazı araştırmacılar ise mediyal, intermediate ve lateral dalların azalan oranlarda bu tünelden geçtiğini raporlamışlardır.…”
Section: Anatomiunclassified
See 2 more Smart Citations
“…Buranın lokalizasyonu orta hatta spinöz çıkıntıların 7-8 cm lateralinde iliyak krest üzerindedir. [4][5][6][7][8][9][10][11][12][13][14][15][16] Anatomi çalışmalarında SKS'nin mediyal dalının osteofibröz tünelden geçmesi ile ilgili tartışmalı veriler vardır. Bazı çalışmalarda, SKS'nin bütün dallarının iliyak krest üzerinde torakolomber fasiyayı deldiği gösterilmiş; karşıt olarak başta Maigne olmak üzere, bazı araştırmacılar tüm mediyal dalların osteofibröz tünelden geçtiğini rapor ederken, diğer bazı araştırmacılar ise mediyal, intermediate ve lateral dalların azalan oranlarda bu tünelden geçtiğini raporlamışlardır.…”
Section: Anatomiunclassified
“…Son anatomi çalışmasında ise Konno, SKS'nin T12-L5 tüm sinir köklerinden köken aldığını ve ayrıca osteofibröz tünelden geçen sinir dallarının özellikle L4-L5 spinal sinir köklerinden orijin aldığını göstermiş ve böylece SKS tuzaklanmasının siyatiği taklit eden bacak semptomlarına yol açması anlaşılabilmiştir. 4 Anatomi çalışmalarında SKSTN, örnek vakalarda %1,8-13 oranında tespit edilmiştir. [5][6][7][8][9][10][11][12] EPiDEMiyOLOji SKSTN prevalansını değerlendiren çok az çalışma mevcuttur.…”
Section: Anatomiunclassified
See 1 more Smart Citation
“…2, 3 Unlike the previous classical descriptions in anatomical textbooks, detailed cadaveric studies have identified not a single medial branch of the SCN passing through the well-known osteo-fibrous tunnel, but multiple tiny branches (variously anastomized like a small nervous plexus) instead. 4 It has also been suggested that such a thin neural network can act as a potential pain generator, not necessarily with the presence of compression in the osteofibrous tunnel, but simply due also to an excessive friction/irritation under the thoracolumbar fascia during lumbar spine movements. 4 In fact, it is well known that neuropathic pain can be generated by neuro-inflammation of a nerve root/peripheral nerve without any compression but simply via chemical mediators and inflammatory cytokines (ie, chemical neuritis/ radiculitis).…”
Section: To the Editormentioning
confidence: 99%
“…4 It has also been suggested that such a thin neural network can act as a potential pain generator, not necessarily with the presence of compression in the osteofibrous tunnel, but simply due also to an excessive friction/irritation under the thoracolumbar fascia during lumbar spine movements. 4 In fact, it is well known that neuropathic pain can be generated by neuro-inflammation of a nerve root/peripheral nerve without any compression but simply via chemical mediators and inflammatory cytokines (ie, chemical neuritis/ radiculitis). 5 This condition may be evoked by several types of mechanical stress on the neural tissues, such as tension, twist, and friction.…”
Section: To the Editormentioning
confidence: 99%